Blockchain technology in energy markets – An interview with the European Energy Exchange - Rainer Alt; Erik Wende (Electronic Markets, 2020)
What is the impact of blockchain technology on electronic markets in the energy sector? In this interview with Electronic Markets, Dr. Tobias Paulun, chief strategy officer of the European Energy Exchange (EEX), explains where the leading European energy exchange recognizes potentials of blockchain technology compared to existing electronic platforms and which blockchain projects EEX is working on. In his view, the impact of blockchain technology depends on the respective market segment and on the availability of solutions for safeguarding guarantees of origin. He expects that established exchange systems and blockchain-based systems will coexist in this strongly regulated and specialized industry.
Keywords: 620; Energy exchange; Power exchange; Decentralized markets; Blockchain technology